IDENTIFICATION AND CULTIVATION OF MFW 23-08 ISOLATED FROM MARINE SPONGES FOR BIOACTIVE COMPOUND PRODUCTION - Chasanah, Ekowati; Pratitis, Asri; Mangunwardoyo, Wibowo (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
Production of marine bioactive compound for commercial usage has been hampered due tothe problem of raw material supply. To overcome this, marine microbes especially those associatedwith the bioactive-compound producer biota, has been explored as bioactive sources, with severaladvantages such as shorter production time, cheaper production cost and avoiding over exploitationof marine biota sources. Previous research showed that fungi MFW 23-08 was one of the potentialisolates from Wakatobi sponges which produced bioactive compounds that was active againstbreast cancer cell line and as antioxidant. This study was intended to identify MFW 23-08 andoptimize the production of its bioactive compound through optimization of MFW 23-08 culture.Culture optimization was conducted using 3 liquid media, i.e. malt extract broth (MEB), glucosepeptone yeast (GPY), and minimal fungal media (MFM), and cultivation periods, i.e. 2, 4, 6, 8, and10 wk. Results revealed that MFW 23-08 crude extract of 2 wk-MFM cultivation, at the concentrationof 30 Î¼g/ml, was able to retard 87% breast cancer (T47D) cell growth. While at concentration of100 Î¼g/ml, the 6 wk. MEB cultivated extract was able to hamper free radicals (56%). However, thecrude extract from MFM media cultivation, in the concentration of 50 and 100 Î¼g/ml was not able toinhibit Escherichia coli and Staphylococcus aureus growth. Based on molecular identificationusing ITS1-ITS4 primers, MFW 23-08 isolate was 99% similar to Â Penicillium citrinum, P.griseofolvum and Penicillium Â sp.